2017
DOI: 10.1186/s12913-017-2631-3
|View full text |Cite
|
Sign up to set email alerts
|

‘Work it out’: evaluation of a chronic condition self-management program for urban Aboriginal and Torres Strait Islander people, with or at risk of cardiovascular disease

Kyly Mills,
Michelle L. Gatton,
Ray Mahoney
et al.

Abstract: BackgroundChronic diseases disproportionately burden Aboriginal and Torres Strait Islander people in Australia, with cardiovascular (CV) diseases being the greatest contributor. To improve quality of life and life expectancy for people living with CV disease, secondary prevention strategies such as rehabilitation and self-management programs are critical. However, there is no published evidence examining the effect of chronic condition self-management (CCSM) group programs for Aboriginal and Torres Strait Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…For example, Askew et al (2016) [32] described the formation of a research advisory group consisting of both Aboriginal community members and experienced researchers who provided research governance and oversight, whereas Treloar et al (2018) [98] described consulting with an Aboriginal advisory group in the program development phase rather than the evaluation process. Consideration of cultural sensitivities was also discussed broadly in some papers, including processes undertaken to build rapport with collaborating Aboriginal communities prior to the conduct of an evaluation [59, 72] and the receipt of cultural guidance or support from a steering group of Aboriginal people or Elders [40, 83].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Askew et al (2016) [32] described the formation of a research advisory group consisting of both Aboriginal community members and experienced researchers who provided research governance and oversight, whereas Treloar et al (2018) [98] described consulting with an Aboriginal advisory group in the program development phase rather than the evaluation process. Consideration of cultural sensitivities was also discussed broadly in some papers, including processes undertaken to build rapport with collaborating Aboriginal communities prior to the conduct of an evaluation [59, 72] and the receipt of cultural guidance or support from a steering group of Aboriginal people or Elders [40, 83].…”
Section: Resultsmentioning
confidence: 99%
“…Programs tailored to young peoples' needs and embedded in communities are required. Primary health care services are a promising setting for diabetes prevention programs (Laatikainen et al 2007), such as the Aboriginal Community Controlled Health Services (ACCHS) sector providing crucial comprehensive care (Panaretto et al 2014) including programs supporting lifestyle changes (Firth et al 2012;Dimer et al 2013;Davey et al 2014;Mills et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies met the inclusion criteria and were included in this review. These included one step-wedged randomised trial with longitudinal sub-study [ 41 , 42 ], one pragmatic randomised trial [ 43 ], one randomised controlled trial [ 44 ], and two pre-post longitudinal quasi-experimental studies [ 45 , 46 ]. The included studies were published between 2012 and 2018 and were written in English language.…”
Section: Resultsmentioning
confidence: 99%
“…The studies took place in a range of locations with widely varied demographic characteristics including: communities in the very remote regions of the Northern Territory [ 41 , 42 ]; urban and regional areas of Western Australia [ 46 ]; as well as metropolitan and rural areas of South Australia [ 43 , 44 ] and south east Queensland [ 45 ]. Three studies reported consultation and collaboration with the communities/populations of interest during the development of projects, and the employment of Indigenous staff in their implementation [ 42 , 44 , 45 ]. Loss to follow-up and poor attendance were a significant issue for several studies ( n = 3) [ 41 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%